Do tax incentives attract foreign direct investment? : the case of the Southern African Development Community - Simon Munongo; Zurika Ribinson (The journal of accounting and management, 2017)
The problem of low domestic savings is inherent in most Southern African Development Community (SADC) countries. This has motivated most of the SADC countries to institute policies that seek to attract foreign capital to cover the investment deficit that arises from low domestic savings rates. In separating individual tax incentives mainly used in the SADC region, this study gives a robust analysis on the impact of each tax incentive on FDI inflows into SADC countries. The tax incentives used in this study are: tax holidays, corporate income tax (CIT), reduced CIT in specific sectors and losses carried forward. The study, in consultation with data from the period 2004 to 2013 separates the SADC countries into four panels based on resource richness. Panel 1 includes the resources-rich countries, Panel 2 the resources-poor countries, Panel 3 all SADC countries, except South Africa and Panel 4 all the SADC countries. The study adopts a system Generalised Method of Moments (SYS GMM) methodology to address the problem of endogeneity associated with dynamic panel data models. The estimated results established that tax holidays positively explain FDI inflows in Panel 2. CIT was found to negatively affect FDI inflows into all SADC countries despite their particular category of resource-richness. Losses carried forward are insignificant in all panels and reduced CIT in specific sectors negatively influences FDI inflows in Panel 1 and surprisingly positively influences FDI inflows in Panel 2.
2668125-0; 2392-8778; The journal of accounting and management; 718053745